Communication Activities On Creating Shared Value (CSV) between Nestle Indonesia and Consumers - Arfika Pertiwi Putri; Nuriyatul Lailiyah; Tandiyo Pradekso; NS Ulfa (Interaksi Online, 2015)
Nestle is a company which connects its business fields on its business chain through acts that help social issues which later was elaborated by Porter and Kreamer in 2006 into creating shared value (CSV). Michael Porter and Mark Kramer then formulate CSV as a business strategy concept to emphasize the importance of place social issues and needs intocompany strategy planning. It includes communication, interaction with consumers via manyways and channels. The purpose of the research is to recognize how communication activities on creating shared value Nestle Indonesia and consumers is carried out. The research used Berlo communication theory, Innovation Diffusion theory, marketing communication, involvement, one-way and two-way communication, and cause related marketing (CRM). The type of the research was qualitative descriptive using grounded research approach and case study as the research method. The result of the research shows that there is a communication strategy in the essence of CSV business strategy of Nestle Indonesia. CSV of Nestle Indonesia consists of agroup of programs where they are derived from marketing communications mix which delivers a consistent message that company’s values are intersected with global consumer’s values (create value). The communication process between consumers and Nestle is a dialog of co-learning and co-creation experience by diffusing innovation and knowledge to customers. Furthermore, there is a co-enrichment, co-production activities inthe CSV activity chain. Key element of the process are relevant contact point, virtual and non-virtual community role, and the role of opinion leaders and formers by sharing responses where customers interact with other customers (C2C). Mass media is also an essential factor to brace the existing values in the CSV programs so that they are more acknowledged by a larger audience. An interconnected network then is built between one element and another creating a communication network.